624 DEALING WITH THE UNKNOWN: A STRANGE CASE OF RECURRENT FEVER. (15th December 2022) - Brugiatelli, Leonardo; Coretti, Francesca; Alfieri, Michele; Bastianoni, Gianmarco; Paolini, Federico; Coraducci, Francesca; Belleggia, Sara; Torselletti, Lorenzo; Barbarossa, Alessandro; Ciliberti, Giuseppe; Principi, Samuele; Di Noto, Giorgio; et al.
Abstract: Blood culture negative endocarditis (BCNE) accounts for 5-10% of all cases of endocarditis. The most common cause of this outcome is initiation of antibiotics prior to cultures. The second most common etiology of negative blood culture is infection secondary to intracellular organisms, which require specific serological tests to be detected. Less frequently, the cause BCNE is noninfectious endocarditis. In this case, it could be secondary to systemic inflammatory diseases or malignancies. We present the case of a 64-year-old male who presented to his physician complaining of fever, malaise and generalized weakness. He was treated with oral antibiotics and with evidence of initial improvement, but after a few days the fever recurred. His past medical history was significant for cardiac surgery: he had an aortic bioprosthesis implanted for severe regurgitation secondary to left coronary cusp prolapse. Furthermore, he underwent mitral and tricuspid valve annuloplasty for severe regurgitation secondary to diffuse prolapse of these valves. After recurrence of the fever, he presented to his local hospital. A CT scan was executed and showed left basal lobe hypoattenuation. Given the context, this finding led to a diagnosis of community-acquired pneumonia. He was then treated accordingly and improved. A few days later, the fever returned, and he went back to his local hospital. This time he was visited by a cardiologist, and a transthoracic echocardiogram showed the presence of a vegetation adherent to the aortic bioprosthetic valve. Revising the initial CT scan, the lobar consolidation initially seen was interpreted retrospectively as an atelectasis. On that same day, due to the presence of a painful red eye, the patient was visited by an ophthalmologist. Retinal examination revealed the presence of lesions strongly suggestive of fungal endophthalmitis. Considering these results, fungal endocarditis was suspected. In view of the patient's complexity and the need for a cardiac surgery, the patient was transferred to our hospital and, after performing blood cultures to identify the pathogen, immediately started on an empirical broad-spectrum antibiotic and antifungal therapy. On admission a cerebral CT scan showed the presence of asymptomatic cerebral septic emboli. Due to the presence of cerebral lesions deemed at high hemorrhagic risk, no immediate surgical indication was posed, despite the suspicion of fungal endocarditis. Fortunately, the patient responded to medical treatment alone. However, blood cultures never revealed the presence of a defined pathogen. Therefore, the final diagnosis was that of blood culture negative endocarditis.